ANALISIS UNJUK KERJA PLTS CARPORT 37,8 KWP DI AREA PERKANTORAN KEMENTERIAN ESDM REPUBLIK INDONESIA JAKARTA PUSAT - Rafhel Panjaitan, Kavlin; Dwi Giriantari, Ida Ayu; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 10 No 1 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i01.p4, 2023)
The utilization of PV in Indonesia increased significantly. Based on data submitted by the Director General of EBTKE, the PV capacity value until first semester of 2021 is 217 MW. New challenge has emerged, namely maintaining performance of the PV system in good condition. Performance of the PV Carport system is analyzed by simulating PV using PVSyst software to see the potential value of electricity production, then calculating the performance parameters of the PV system such as Yield Factor (Yf), Yield Reference (Yr), Performance Ratio (PR) and Capacity Factor (CUF). Then compared with the results of electricity production and performance parameters of the PV system during operation for one year. The object of research on performance of the 37.8 kWp Carport PV system belonging to Ministry of Energy and Mineral Resources. Based on the PVSyst simulation results, the potential annual electrical energy from the Carport PV system is 53,910 kWh with performance parameters (Yf, Yr, PR, and CUF) respectively 1,426.19 kWh/kWp, 1,751.9 kWh/kW, 81.4% and 16%. The production value of the Carport PV system for a year in 2021 is 21,694.67 kWh with performance parameters (Yf, Yr, PR, and CUF) respectively of 573 kWh /kWp, 1,679.9 kWh/kW, 34% and 6.6%.